Increased resistance to apoptosis during differentiation and syncytialization of BeWo choriocarcinoma cells - Wei, Bih-Rong (Adv Biosci Biotechnol, 2012)
Transition from mononuclear villous cytotrophoblast into multinuclear syncytiotrophoblast in the human placenta is accompanied by changes in apoptosis-related proteins and an apparent increased resistance to induced apoptosis. We investigated the specific nature and timing of changes in Bcl-2, Bax, p53, and caspases 3 and 8 in forskolin-treated BeWo choriocarcinoma cells, a model for villous cytotrophoblast differentiation. BeWo cells were treated with forskolin or vehicle alone for up to 72 h and evaluated at 24 h intervals for syncytialization and quantitative expression specific apoptosis-related proteins and mRNAs. Syncytialization was quantified using fluorescent staining of intercellular membranes and enumeration of the percentage of nuclei in multinucleate cells, and differential localization of apoptosis-related proteins to multinuclear or mononuclear cells was determined by quantitative immunofluorescence. Forskolin treatment for up to 72 h resulted in 80% syncytialization, increased expression of Bcl-2 protein (P < 0.01) and mRNA (P < 0.05), and significantly decreased expression of protein and mRNA for Bax, p53, and caspases 3 and 8. Syncytialized cells expressed higher levels of Bcl-2 protein concurrent with increased resistance to cisplatin-induced apoptosis. Thus, syncytialization of BeWo cells was accompanied by altered transcription of apoptotic-related proteins characteristic of increased apoptosis resistance secondary to increased expression of the anti-apoptotic protein Bcl-2 and diminish expression of pro-apoptotic proteins.